Computational CAM: studying children and media in the age of big data. Issue 1 (2nd January 2016) - Foucault Welles, Brooke
Abstract: New media technologies enable the pervasive and unobtrusive tracking of children's media use and interaction behaviors, and a host of new opportunities that researchers are only beginning to embrace. The possibilities for unlocking longstanding questions about children and media are thrilling, but the path forward is complicated by questions about epistemology, data, ethics and training. In this essay, I outline the promise and peril of computational social science for children and media research, drawing on advances from related fields to offer suggestions for researchers hoping to make use of big data and computational analytics.